2004
DOI: 10.1111/j.1469-0691.2004.00942.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance of Acinetobacter spp. in Europe

Abstract: Bacteria of the genus Acinetobacter are ubiquitous in nature. These organisms were invariably susceptible to many antibiotics in the 1970s. Since that time, acinetobacters have emerged as multiresistant opportunistic nosocomial pathogens. The taxonomy of the genus Acinetobacter underwent extensive revision in the mid-1980s, and at least 32 named and unnamed species have now been described. Of these, Acinetobacter baumannii and the closely related unnamed genomic species 3 and 13 sensu Tjernberg and Ursing (13T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
207
2
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(224 citation statements)
references
References 142 publications
3
207
2
6
Order By: Relevance
“…Infections caused by Acinetobacter species are acquired due to hospitalization, mechanical ventilation, respiratory failure, inadequate treatment, previous infection, or antibiotic therapy and catheterization (3) . Higher colonization rates of the throat, and respiratory and digestive tracts are well documented in several previous outbreaks (4) (5) .…”
Section: Introductionmentioning
confidence: 78%
“…Infections caused by Acinetobacter species are acquired due to hospitalization, mechanical ventilation, respiratory failure, inadequate treatment, previous infection, or antibiotic therapy and catheterization (3) . Higher colonization rates of the throat, and respiratory and digestive tracts are well documented in several previous outbreaks (4) (5) .…”
Section: Introductionmentioning
confidence: 78%
“…Very important place of their occurrence is the hospital environment, especially intensive care units [10,43,113,132]. Acinetobacters are the second most commonly isolated nonfermenters in human specimens (Pseudomonas being the first).…”
Section: Introduction -Acinetobacter Baumanniimentioning
confidence: 99%
“…Reports of carbapenem resistance in Acinetobacter baumannii have accumulated worldwide (11,14,21). Most of these studies showed that ␤-lactamase-mediated resistance is the most common mechanism for carbapenem resistance in that species.…”
mentioning
confidence: 99%